Sodomy in Early 20th-Century Costa Rica: Prophylactic Episteme and Biopolitical Intervention in Social Space. - Gómez-Solano, Paulo (2023)
This paper argues, based on a sample of sodomy cases processed between 1900 and 1922, that between the end of the 19th century and the beginning of the 20th century, a prophylactic episteme emerged in the country. This episteme will be responsible for the simultaneous and harmonious unfolding of social sanitization apparatuses and legal apparatuses that will aim to a “dangerous subject” as that in which characteristics of perversion, disease and degeneration are condensed in the same body, and which, in this case, calcifies in the sodomite. It concludes that these devices operated together to create spaces for biopolitical intervention.